FDI in Hungary: The first mover's advantage and disadvantage - Magdolna Sass (EIB Papers, 2004)
Presenting a case study of FDI in Hungary, this paper first reviews the characteristics of FDI in Hungary since the outset of transition. It then examines the determinants of FDI in Hungary, finding that early and comprehensive privatisation and the creation of a generally business-friendly policy environment played key roles in making Hungary an early leader in FDI flows to countries in Central and Eastern Europe. But the paper also observes that some of Hungary's first-mover advantage has been eroded in recent years as other countries have provided increasingly friendly environments for FDI, often combined with lower labour costs. The paper then proceeds to assess the influence of FDI on Hungary's economy. It concludes that FDI has had, on balance, a positive impact on economic performance although hard evidence of spillovers to indigenous firms is difficult to find.
Keywords: 330; Direktinvestition; Übergangswirtschaft; Arbeitskosten; Standortwettbewerb; Spillover-Effekt; Ungarn